2005
DOI: 10.1002/ange.200500343
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of [exo‐BH2(Cp*M)2B9H14] (M=Ru, Re), and the Conversion of the Ruthenaborane into [(Cp*Ru)2B10H16] with an Open Cluster Framework Based on a Capped Truncated Tetrahedron

Abstract: The evolution of main-group and transition-metal cluster structural chemistry since the development of the electroncounting rules in the 1970s is an important achievement of modern inorganic chemistry. [1,2] The useful connection between cluster geometry and electronic structure defined by the electron counting rules provides a solid foundation for the rational approach to larger clusters and nanoparticle systems that lie between small clusters and bulk crystalline materials with extended structures. [3] Given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Synthesis and characterization of oxavanadaborane 6 and vanadaborane 7 : Recently, we reported the synthesis of divanadaborane from the thermolysis of [Cp 2 VCl 2 ] with LiBH 4 ⋅ THF and a monoborane reagent 10. Interestingly, this result, as well as the existence of higher‐nuclearity rhenaboranes25 and ruthenaboranes,26 led us to revisit the vanadium system that yielded compounds 6 and 7 (Scheme ). The molecular structure of compound 6 (Figure 4) clearly shows that one ethoxy group is bound to two V metal atoms and one B atom.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis and characterization of oxavanadaborane 6 and vanadaborane 7 : Recently, we reported the synthesis of divanadaborane from the thermolysis of [Cp 2 VCl 2 ] with LiBH 4 ⋅ THF and a monoborane reagent 10. Interestingly, this result, as well as the existence of higher‐nuclearity rhenaboranes25 and ruthenaboranes,26 led us to revisit the vanadium system that yielded compounds 6 and 7 (Scheme ). The molecular structure of compound 6 (Figure 4) clearly shows that one ethoxy group is bound to two V metal atoms and one B atom.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we reported the synthesis of divanadaborane from the thermolysis of [Cp 2 VCl 2 ] with LiBH 4 ·THF and a monoborane reagent. [10] Interestingly, this result, as well as the existence of higher-nuclearity rhenaboranes [25] and ruthenaboranes, [26] led us to revisit the vanadium system that yielded compounds 6 and 7 (Scheme 3). The molecular structure of compound 6 ( Figure 4) clearly shows (5), Nb1-B2 2.470(5), Nb1-B3 2.486(5), Nb1-B4 2.423(3), Nb1-S1 2.4390 (14), B1-B4 1.775 (7), B2-B3 1.701(8), B1-S1 1.809(6); Nb1-S1-Nb2 70.12(4), S1-B1-B4 124.2(3), Nb1-B1-Nb2 69.56 (14).…”
Section: Synthesis and Characterization Of Oxavanadaborane 6 And Vanamentioning
confidence: 99%
“…Recently we have shown that the reaction of [(Cp*Ru) 2 B 3 H 9 ] with BH 3 ⋅THF leads to metallaboranes containing six, eight, and ten boron atoms 13. 14 The ten boron atom cluster has two colorless isomeric forms, one with an exo‐cluster borane atom on a Ru 2 B 9 cluster framework. This species was shown to be an intermediate on the path to the second isomer which has a Ru 2 B 10 cluster framework.…”
Section: Methodsmentioning
confidence: 99%
“…This approach has led to the isolation of [(1‐Cp*Ru)B 5 H 10 ] ( 1 ; in which the Cp*Ru fragment occupies the 1‐position of the BH cage) and [(Cp*Ru)B 8 H 14 (RuCp*)] ( 2 ). Metallabarane 2 converts into the isomer pair [(Cp*Ru) 2 B 10 H 16 ]14 on heating in the presence of BH 3 ⋅THF showing that it is indeed another intermediate in the cluster‐building process.…”
Section: Methodsmentioning
confidence: 99%
“…With regard to systematic cluster expansion, the most versatile metal is rhenium, and known Re 2 B n frameworks with n =4–10 23a. Fewer compounds are known with ruthenium23b and rhodium,25 but use of a large excess of BH 3 ⋅THF and harsh conditions enables the isolation of 16‐vertex rhodaborane 1 as a moderately stable yellow crystalline solid. The identity of 1 was confirmed by multinuclear NMR spectroscopy, elemental analysis, infrared spectroscopy, and X‐ray structural analysis (Figure 2).…”
mentioning
confidence: 99%